Association between Interleukin-5 & Body Mass Index among Iraqi Asthmatic Patients - Al-Rubayei, Yacoob Y.; Al-Haidary, Batool A.; Jasim, Wala'a E. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Asthma is an allergic hypersensitivity disease in which many mediators play a role in its pathogenecity. One of these etiological agents is the mediators such as Interleukin-5 (IL-5).The  aim of this study to demonstrate the association between IL-5 and obesity in asthma development. Materials & Methods: One hundred and four sera samples for asthma cases have been studied in comparison with 41 non-asthmatic bronchitis as a patient controls beside 30 apparently healthy controls. Cytokine has been estimated using ELISA method in correlation with Body Mass Index (BMI).Results: This study revealed a significant correlation between IL-5 concentration and BMI (P